Peran Penyuluh Pertanian Dalam Pengembangan Kelompok Tani Jagung Di Desa Warembungan Kecamatan Pineleng Kabupaten Minahasa - Tumbel, Marc Asyer; Manginsela, Elsje Pauline; Rori, Yolanda Pinky Ivanna (Sam Ratulangi University, 2024)
The purpose of this study was to examine the role of agricultural extension officers in the development of Maize farmer groups in Warembungan Village, Pineleng District, Minahasa Regency. This research was conducted for 3 months, starting from September to November 2023. The research was conducted in Warembungan Village, Pineleng District, Minahasa Regency. Data collection methods were carried out using primary data obtained by direct interview to the respondents, using a questionnaire. Secondary data was obtained from agencies related to the research as well as various literature in accordance with the research objectives. The sampling method used was purposive sampling. The sample size was 15 respondents who were the head and members of the Werot Farmer Group. Warembungan Village has 6 Farmer Groups, but there is only 1 active Farmer Group, namely the Werot Farmer Group. Data analysis used in this research is quantitative descriptive analysis using Likert scale measurements. The results showed that the level of the role of extension workers as motivators, dynamicators, facilitators, innovators, educators, and developers of farmer groups in Warembungan Village, Pineleng Subdistrict, Minahasa Regency was classified in the moderate category, with an average value of 55.38 percent.